Australia's remote workfare policy: Rhetoric versus reality of 'community' empowerment. (February 2021) - Staines, Zoe
In 1977, Jones (in Bryson and Mowbray, 1981: 255) described the term 'community' as 'the aerosol word of the 1970s because of the hopeful way it is sprayed over deteriorating institutions.' They argued that the term is used to give the impression of community ownership over policymaking processes and outputs when the reality can be far different. This article discusses one of Australia's current workfare programs, the Community Development Programme (CDP), which operates in remote parts of the country as new welfare conditionality architecture for moving (mainly Indigenous) remote unemployed people off welfare and into work. It argues that, despite political rhetoric to the contrary, 'community' is marginalised in the program's design and implementation. Instead, CDP can be best conceptualised as a manifestation of neoliberal paternalism, whereby the governance practices of the state work through community organisations to enforce market principles and 'train' unemployed and poor people into pursuing 'freedom' within the bounds of market rationality. Through these modes of governing, Indigenous communities are instead strategically disempowered.